Single Nucleotide Polymorphism of Thyroid Hormone Receptor a Gene can be a Risk of Atherogenic Dyslipidemia - Satwika Sinha; Kaushik Kar (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Dyslipidemia and atherosclerosis are common occurrence in hypothyroidism. Not all patients suffering from hypothyroidism present alteration of lipid profile pertinent to atherogenesis characterised by high cholesterol, triglyceride and low HDLc levels. Genetic predisposition may play a vital role in developing dyslipidemia among hypothyroid patients. Some association studies have identified the variations in thyroid hormone receptor α gene in developing complications like obesity, dyslipidemia, and coronary atherosclerosis in hypothyroid patients. Aim: To find the association between Thyroid Hormone Receptor (THR) α gene variations and atherogenic dyslipidemia. Materials and Methods: This cross-sectional, observational hospital based study was conducted to examine the status of atherogenic lipid profile in hypothyroid state, the study analysed the genotyping of rs 939348 Single Nucleotide Polymorphism (SNP) in normolipidemic and dyslipidemic hypothyroid patients. The study compared THR α polymorphism genotype and allele frequencies in above mentioned two groups with unpaired t-test and ANOVA (Odds ratio, p<0.05). Furthermore the study compared the serum triglyceride and HDLc levels between different genotype and allele groups (p<0.05). Results: The study observed rs939348 SNP was associated with significantly high fasting triglyceride and low HDLc levels (p<0.05). Furthermore the study observed the trend of increase in mutant T allele in dyslipidemic hypothyroids. Conclusion: The study proved the role of THR α genotyping in predicting atherogenic dyslipidemia among hypothyroids.